Endometriosis in adolescents - O.V. Fedorenko; Yu.S. Ocheretna; H.P. Tarnovska (Zaslavsky O.Yu., 2024)
Endometriosis is one of the most significant disorders affecting women of all ages, including adolescents. Its prevalence is estimated at an average of 15 %, but data in adolescents is lacking and the real data may be significantly higher. Endometriosis in adolescents is a global medical, social and economic problem, as the associated symptoms worsen the quality of life, reduce the level of socialization, have negative impact on health indicators and quality of life, affect future reproductive capabilities and increase economic costs. For a long time, endometriosis was considered as a disease of women of reproductive age; however, now it is known that it affects women of all ages. In adolescent girls, endometriosis is understudied, sometimes ignored, or unrecognized that leads to delays in diagnosis and, consequently, in treatment. The aim of this review was to analyze clinical manifestations of endometriosis in adolescents, factors associated with the risk of development and progression of the disease, and the peculiarities of diagnosis and treatment in adolescence. Understanding the features of this disease, its symptoms, diagnosis, and treatment in adolescents will significantly improve the quality of life, control the disease, and enhance future reproductive capabilities.